Answer:
Step-by-step explanation:
Answer:
-2
Step-by-step explanation:
[3-(-1)]/[2-4] = -2
I may be wrong but I think it is "True"
Take away 3 from both sides,
x+3<-2
-3 -3
=x<-5
answer=x<-5
hope this helps.......
Answer:
<em>x = - √10, and x =√10</em>
Step-by-step explanation:
1. Let us add 3 to either side of the equation: x^2 - 3 + 3 = 7 + 3
2. That equation would simplify to: x^2 = 10
3. Now let us take the square root on either side: √x^2 = √10
4. Being square root of x^2, we could say that: | x | = √10
5. And thus 2 answer may be derived from this equation provided absolute value symbol ( | | ): <em>x = - √10, and x =√10</em>